2015
DOI: 10.1016/j.joa.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial thrombus formation and resolution during dabigatran therapy: A Japanese Heart Rhythm Society report

Abstract: LA thrombus developed in 4% of patients with AF receiving Dabi. Older patients with a higher CHADS2 score receiving a lower Dabi dosage were more likely to develop LA thrombus, which was resolved with a prolonged or increased dosage. A higher Dabi dosage may be more beneficial before ECV but prospective randomized studies would be needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
1
19
0
3
Order By: Relevance
“…Several recent studies have reported the percentage of LAT on TEE ranging from 2.1% to 4.4% in AF patients on DOACs before catheter ablation. [19][20][21][22][23] There was no difference in the prevalence of LAT between patients with DOACs and those with warfarin. 19,20 Mitamura et al 22 identified 4% LAT in persistent AF patients on dabigatran undergoing electrical cardioversion.…”
Section: Prevalence Of Lat In Af Patients On Doacsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have reported the percentage of LAT on TEE ranging from 2.1% to 4.4% in AF patients on DOACs before catheter ablation. [19][20][21][22][23] There was no difference in the prevalence of LAT between patients with DOACs and those with warfarin. 19,20 Mitamura et al 22 identified 4% LAT in persistent AF patients on dabigatran undergoing electrical cardioversion.…”
Section: Prevalence Of Lat In Af Patients On Doacsmentioning
confidence: 99%
“…In the present study, the rate of LAT was 4.4% in AF patients on DOACs, almost similar to or even higher than the rate in the prior reports. [19][20][21][22][23] In the previous studies, DOACs were not evenly distributed, likely stemming from the later introduction of apixaban and edoxaban for clinical use compared with dabigatran and rivaroxaban during the study period. However, in the present study, the 4 DOACs were evenly distributed, and the number of patients on apixaban treatment with LAT was relatively higher.…”
Section: Prevalence Of Lat In Af Patients On Doacsmentioning
confidence: 99%
“…To date, Mitamura et al reported that LAA thrombi were observed in 4% of Japanese AF patients on dabigatran. 17 In 21% of their patients, dabigatran was used for <3 weeks prior to the TEE. To our knowledge, this is the first report on the prevalence of LAA thrombi in Japanese patients during anticoagulation therapy including all 4 currently available not.…”
Section: Prevalence Of Laa Thrombi During Anticoagulationmentioning
confidence: 99%
“…По данным T.Wallacе et al частота выявления тромба УЛП у пациентов с ФП на фоне приема антикоагулянтов составляет 3,6% [38]. В работе H.Mitamura et al по оценке эффективности терапии дабигатраном в отношении профилактики тромбообразования в УЛП частота выявления тромбоза УЛП составила 4% (8 пациентов) [39].…”
Section: антикоагулянтная терапия и тромбоз ушка левого предсердияunclassified